Gene spectrum and clinical traits of 10 patients with primary carnitine deficiency. Issue 2 (9th February 2021) - Chen, Yao; Lin, Qingying; Zeng, Yinglin; Qiu, Xiaolong; Liu, Guanghua; Zhu, Wenbin
Abstract: Background: Rare studies focused on the tandem mass spectrometry (MS/MS) findings for the primary carnitine deficiency (PCD) in the neonates in China mainland. In this study, we aim to analyze the gene mutation spectrum of PCD in Fujian Province in China mainland. Methods: Primary carnitine deficiency (PCD) samples used in this study were selected from 95, 453 cases underwent neonatal screening between May 2015 and February 2020. SLC22A5 gene sequencing was performed on the neonates and their parents with C0 level of less than 8.8 μmol/L. Results: Ten patients (male: 7; female: 3) were finally included in this study. Among these patients, nine were neonates, and one was maternal decline of C0 of less than 8.8 μmol/L. The maternal case showed two types of mutations of SLC22A5 including c.760C>T(p.R254*) and c.1400C>G(p.S467C). The other nine neonates showed compound mutations involving nine types in 18 sites, among which two mutations [i.e., c.37G>T(p.E13*) and c.694A>G(p.T232A)] were novel that had never been reported before. Bioinformatic analysis indicated that c.37G>T(p.E13*) was a pathogenic mutation, while the c.694A>G (p.T232A) was considered to be likely pathogenic. Conclusion: MS/MS screening on PCD contributed to the early diagnosis and screening. In addition, SLC22A5 gene mutation analysis contributed to the PCD screening. Abstract : MS/MS screening on PCD contributed to the early diagnosis and screening. In addition, SLC22A5 gene mutation analysis contributed to the PCD screening.